(untitled) (Global Journal of Management and Business Research, 2021)
Cybercrime becomes costlier than physical crime in developed economies. As a result, it has become the top priority in governance issues in financial institutions. As a developing nation in Bangladesh, the banking sector faces multi-dimensional challenges to adopt IT applications in banking with cybercrime. The paper examines what the banking industry faces cyber security risks and how the board members contribute to identify and mitigate the risk. Through an in-depth interview among the directors of commercial banks in Bangladesh, we identified the possible cyber risk and prepared the risk profile describing the sources, implications, severity of impact, likelihood of occurrence and ranked them. The result shows that the IT governance risk, IT investment risk, and information risk are most critical among the significant cyber security risks. The results of the study have important implications for both corporate boards and policymakers.